Polyimide, resin composition, resin film, laminate, coverlay film, resin-coated copper foil, metal-clad laminate, and circuit board

By formulating polyimides with specific diamine residues and incorporating additional components, the challenges of achieving low dielectric loss tangent and excellent adhesion in high-frequency applications are addressed, resulting in improved performance for electronic equipment.

JP7655752B2Active Publication Date: 2025-04-02NIPPON STEEL CHEM & MATERIAL CO LTD
View PDF 12 Cites 0 Cited by

Patent Information

Application Number
JP2021052518
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-03-26
Publication Date
2025-04-02
Estimated Expiration
2041-03-26

AI Technical Summary

Technical Problem

Existing polyimides made from dimer diamine as a raw material exhibit excellent adhesion and handling but fail to meet the requirement of low dielectric loss tangent necessary for high-frequency applications.

Method used

The development of polyimides containing tetracarboxylic acid residues and diamine residues derived from dimer diamine, with a biphenyl or naphthalene skeleton, and incorporating a crosslinking agent, elastomer resin, and polymerization initiator to achieve low dielectric loss tangent and excellent adhesion.

Benefits of technology

The resulting resin composition and film demonstrate improved high-frequency properties, adhesion, solder heat resistance, and flame retardancy, making them suitable for high-speed signal transmission in electronic equipment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007655752000001
    Figure 0007655752000001
  • Figure 0007655752000002
    Figure 0007655752000002
  • Figure 0007655752000003
    Figure 0007655752000003
Patent Text Reader

Abstract

To provide polyimide which uses dimer diamine as a raw material and enables formation of a resin film having both low dielectric loss tangent and excellent adhesion.SOLUTION: Polyimide contains: 40 mol% or more and 95 mol% or less a diamine residue derived from a dimer diamine composition containing dimer diamine, which is obtained by substituting a primary aminomethyl group or an amino group for each of two terminal carboxylic acid groups of a dimer acid, as a main component with respect to the total of diamine residues; and contains 5 mol% or more and 25 mol% or less of a diamine residue that is derived from a diamine compound, which contains a biphenyl skeleton or a naphthalene skeleton, where the biphenyl skeleton or the naphthalene skeleton has a substituent having at least one or more inter-carbon double bonds selected from the group consisting of a vinyl group, an acrylic group, a methacrylic group and an allyl group.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a polyimide useful as an adhesive in circuit boards such as printed wiring boards, a resin composition, a resin film, a laminate, a coverlay film, a copper foil with resin, a metal-clad laminate, and a circuit board. [Background technology]

[0002] In recent years, with the progress of miniaturization, weight saving, and space saving of electronic devices, there is an increasing demand for flexible printed circuits (FPCs) that are thin, lightweight, flexible, and have excellent durability even when repeatedly bent. Because FPCs allow three-dimensional and high-density mounting even in a limited space, their applications are expanding to include wiring for moving parts of electronic devices such as HDDs, DVDs, and mobile phones, as well as components such as cables and connectors.

[0003] Polyimide, which has excellent heat resistance, chemical resistance, flexibility, mechanical properties, and electrical properties, is widely used as a material for insulating resin layers constituting circuit boards such as FPCs. In addition, various additives have been added to improve the functionality of polyimide. For example, an adhesive composition has been proposed that is excellent in adhesion, heat resistance, flame retardancy, and handling properties, and has high insulation reliability, by combining a specific phosphorus compound with polyimide (Patent Document 1).

[0004] In addition to higher density, the performance of devices has improved, and so it is also necessary to accommodate higher frequencies of transmission signals. In the fields of information processing and information communication, efforts are being made to increase the transmission frequency in order to transmit and process large volumes of information, and printed circuit board materials are being required to reduce transmission loss by thinning the insulating layer and improving the dielectric properties of the insulating layer. In the future, there will be an increasing demand for insulating layers (including adhesive layers) that make up FPCs to reduce transmission loss and accommodate higher frequencies. In order to improve the dielectric properties of printed circuit board materials, a resin composition has been proposed that contains a multifunctional vinyl aromatic polymer and a thermosetting compound, but does not contain a radical polymerization initiator (Patent Document 2).

[0005] Incidentally, it has been proposed to apply a crosslinked polyimide resin obtained by reacting a thermoplastic polyimide made from a diamine compound derived from a dimer diamine derived from a dimer acid (dimer fatty acid) with an amino compound having at least two primary amino groups as functional groups to an adhesive layer of a coverlay film (Patent Document 3). In the examples of Patent Document 3, it is also disclosed that flaky talc is blended with a thermoplastic polyimide composition made from a dimer diamine. Here, the dimer acid is a dimerized fatty acid obtained by subjecting natural fatty acids such as soybean oil fatty acid, tall oil fatty acid, rapeseed oil fatty acid, and the like, which are refined from these, to a Diels-Alder reaction, and it is known that a polybasic acid compound derived from a dimer acid is obtained as a composition of the fatty acid as a raw material and a fatty acid that is trimerized or higher (Patent Document 4). [Prior art documents] [Patent documents]

[0006] [Patent Document 1] Patent No. 6733845 [Patent Document 2] International Publication No. WO2020 / 175537 [Patent Document 3] Patent No. 5777944 [Patent Document 4] JP 2017-137375 A Summary of the Invention [Problem to be solved by the invention]

[0007] Polyimides made from dimer diamine are soluble in solvents, have excellent adhesive properties, and are easy to handle, making them useful resin materials as adhesives. However, in order to keep up with the future trend toward higher frequencies, in addition to satisfying the above-mentioned properties, there is a demand for even lower dielectric tangents.

[0008] Therefore, an object of the present invention is to provide a polyimide which uses dimer diamine as a raw material and can be used to form a resin film having both a low dielectric tangent and excellent adhesiveness. [Means for solving the problem]

[0009] The polyimide of the present invention is a polyimide containing a tetracarboxylic acid residue derived from a tetracarboxylic acid anhydride component and a diamine residue derived from a diamine component. The polyimide of the present invention contains diamine residues derived from a dimer diamine composition mainly composed of a dimer diamine in which two terminal carboxylic acid groups of a dimer acid are substituted with primary aminomethyl groups or amino groups, in an amount in the range of 40 mol % to 95 mol % relative to the total diamine residues. The polyimide of the present invention contains, relative to all diamine residues, diamine residues derived from a diamine compound which contains a biphenyl skeleton or a naphthalene skeleton, and the biphenyl skeleton or the naphthalene skeleton has at least one substituent having a carbon-carbon double bond selected from the group consisting of a vinyl group, an acrylic group, a methacrylic group, and an allyl group, in an amount within the range of 5 mol % to 25 mol %.

[0010] The resin composition of the present invention comprises the following components (A) and (B): (A) the polyimide, and (B) a crosslinking agent, and the content of the (B) component is within the range of 5 parts by weight or more and 30 parts by weight or less per 100 parts by weight of the (A) component.

[0011] The resin composition of the present invention further comprises the following component (C): (C) an elastomer resin; The content of the (C) component relative to 100 parts by weight of the (A) component may be within the range of 5 parts by weight or more and 100 parts by weight or less.

[0012] The resin composition of the present invention further comprises the following component (D): (D) a polymerization initiator, The content of the (D) component per 100 parts by weight of the (A) component may be within the range of 0.5 parts by weight or more and 2.0 parts by weight or less.

[0013] The resin film of the present invention contains the above-mentioned polyimide.

[0014] The resin film of the present invention may have a dielectric loss tangent (Tan δ) of less than 0.002 at 10 GHz measured with a split post dielectric resonator (SPDR) after being conditioned for 24 hours under constant temperature and humidity conditions (normal state) of 23° C. and 50% RH.

[0015] The laminate of the present invention is a laminate having a substrate and an adhesive layer laminated on at least one surface of the substrate, the adhesive layer being made of the above-mentioned resin film.

[0016] The coverlay film of the present invention is a coverlay film having a coverlay film material layer and an adhesive layer laminated on the coverlay film material layer, and the adhesive layer is made of the above-mentioned resin film.

[0017] The resin-coated copper foil of the present invention is a resin-coated copper foil in which an adhesive layer and a copper foil are laminated together, and the adhesive layer is made of the above-mentioned resin film.

[0018] The metal-clad laminate of the present invention is a metal-clad laminate having an insulating resin layer and a metal layer laminated on at least one surface of the insulating resin layer, and at least one of the insulating resin layers is made of the above-mentioned resin film.

[0019] The circuit board of the present invention is obtained by wiring the metal layer of the metal-clad laminate. Effect of the Invention

[0020] The polyimide of the present invention contains a diamine residue derived from a dimer diamine composition and a diamine residue derived from a diamine compound having a substituent with a carbon-carbon double bond, and therefore can form a resin film having excellent high-frequency characteristics, as well as sufficient adhesiveness (particularly peel strength), solder heat resistance, and flame retardancy for practical use. Therefore, the resin composition and resin film of the present invention can be particularly suitably used as a circuit board material such as an FPC in electronic devices that require high-speed signal transmission. In addition, by improving the dielectric properties of the resin film, it becomes possible to apply it to a direct conversion type receiver. Furthermore, it can be applied to electronic devices of any structure as a highly reliable low-dielectric adhesive. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0021] Hereinafter, an embodiment of the present invention will be described.

[0022] [Polyimide] A polyimide according to an embodiment of the present invention is a polyimide having adhesive properties. Hereinafter, the polyimide according to the present embodiment may be referred to as an "adhesive polyimide". The adhesive polyimide contains a tetracarboxylic acid residue derived from a tetracarboxylic dianhydride component and a diamine residue derived from a diamine component. When the raw materials, tetracarboxylic dianhydride and diamine compound, are reacted in approximately equal moles, the types and molar ratios of the tetracarboxylic acid residues and diamine residues contained in the polyimide can be made to correspond approximately to the types and molar ratios of the raw materials. In the present invention, the term "polyimide" refers to a resin made of a polymer having an imide group in the molecular structure, such as polyimide, polyamideimide, polyetherimide, polyesterimide, polysiloxaneimide, polybenzimidazoleimide, etc. The tetracarboxylic acid residue and the diamine residue constituting the adhesive polyimide will be described below together with their raw materials.

[0023] (acid anhydride) The adhesive polyimide can be made of any tetracarboxylic dianhydride that is generally used as a raw material for polyimides, without any particular limitation. Examples of tetracarboxylic acid residues derived from such tetracarboxylic dianhydrides include 3,3',4,4'-, 2,3',3,4'-, 2,2',3,3'-, or 2,3,3',4'-benzophenonetetracarboxylic dianhydride, 3,3',4,4'-biphenyltetracarboxylic dianhydride (BPDA), 3,3',4,4'-diphenylsulfonetetracarboxylic dianhydride (DSDA), 4,4'-oxydiphthalic anhydride (ODPA), 4,4'-(hexafluoroisopropylidene)diphthalic anhydride (6FDA), 2,2-bis[4-(3,4-dicarboxyphenoxy)phenyl]propane dianhydride (BPADA), p-phenylenebis(trimellitic monoester acid anhydride) (TAHQ), and ethylene glycol. Bis-anhydrotrimellitate (TMEG), pyromellitic dianhydride, 2,3',3,4'-biphenyltetracarboxylic dianhydride, 2,3',3,4'-diphenylethertetracarboxylic dianhydride, bis(2,3-dicarboxyphenyl)ether dianhydride, 3,3'',4,4''-, 2,3,3'',4''- or 2,2'',3,3''-p-terphenyltetracarboxylic dianhydride, 2,2-bis(2,3- or 3,4-dicarboxyphenyl)-propane dianhydride, bis(2,3- or 3,4-dicarboxyphenyl)methane dianhydride, bis(2,3- or 3,4-dicarboxyphenyl)sulfone dianhydride, 1,1-bis(2,3- or 3,4-dicarboxyphenyl) phenyl)ethane dianhydride, 1,2,7,8-, 1,2,6,7- or 1,2,9,10-phenanthrene-tetracarboxylic dianhydride, 2,3,6,7-anthracene tetracarboxylic dianhydride, 2,2-bis(3,4-dicarboxyphenyl)tetrafluoropropane dianhydride, 1,2,5,6-naphthalene tetracarboxylic dianhydride, 1,4,5,8-naphthalene tetracarboxylic dianhydride, 2,3,6,7-naphthalene tetracarboxylic dianhydride, 4,8-dimethyl-1,2,3,5,6,7-hexahydronaphthalene-1,2,5,6-tetracarboxylic dianhydride, 2,6- or 2,7-dichloronaphthalene-1,4,5,8-tetracarboxylic dianhydride, 2,3,6,7-(or 1,4,5,8-)tetrachloronaphthalene-1,4,5,8-(or 2,3,6,7-)tetracarboxylic dianhydride, 2,3,8,9-, 3,4,9,10-, 4,5,10,11- or 5,6,11,12-perylene-tetracarboxylic dianhydride, pyrazine-2,3,5,6-tetracarboxylic dianhydride, pyrrolidine-2,3,4,5-tetracarboxylic dianhydride, thiophene-2,3,4,5-tetracarboxylic dianhydride, 4,4'-bis(2,3-dicarboxyphenoxy)dianhydride Examples of the tetracarboxylic acid residue include tetracarboxylic acid residues derived from aromatic tetracarboxylic dianhydrides such as phenylmethane dianhydride, and tetracarboxylic acid residues derived from aliphatic tetracarboxylic dianhydrides such as 1,2,3,4-cyclobutane tetracarboxylic dianhydride, 1,2,3,4-cyclopentane tetracarboxylic dianhydride, 1,2,4,5-cyclohexane tetracarboxylic dianhydride, 1,2,4,5-cycloheptane tetracarboxylic dianhydride, and 1,2,5,6-cyclooctane tetracarboxylic dianhydride. Among these, 3,3',4,4'-benzophenonetetracarboxylic dianhydride (BTDA), 3,3',4,4'-biphenyltetracarboxylic dianhydride (BPDA), and 4,4'-(hexafluoroisopropylidene)diphthalic anhydride (6FDA), which have a large effect of lowering the dielectric tangent, are preferred, and 3,3',4,4'-biphenyltetracarboxylic dianhydride (BPDA) and 4,4'-(hexafluoroisopropylidene)diphthalic anhydride (6FDA) are more preferred.

[0024] (Diamine) The adhesive polyimide may be made of any diamine compound generally used in polyimides as a raw material, without any particular limitation, but contains 40 mol % to 95 mol %, preferably 70 to 90 mol %, of diamine residues derived from a dimer diamine composition mainly composed of a dimer diamine in which two terminal carboxylic acid residues of a dimer acid are substituted with primary aminomethyl groups or amino groups, relative to the total diamine residues. By containing the diamine residues derived from the dimer diamine composition within the above range, the solubility of the polyimide can be improved, and the relative dielectric constant and dielectric loss tangent can be reduced. If the content of the diamine residues derived from the dimer diamine composition is less than 40 mol% relative to the total diamine residues, the relative dielectric constant and dielectric loss tangent tend to increase due to the relatively increased polar groups contained in the polyimide. In addition, by containing the diamine residues derived from the dimer diamine composition in the above amount, it is possible to improve the thermocompression bonding properties by lowering the glass transition temperature (lowering Tg) of the polyimide and to alleviate the internal stress by lowering the elastic modulus. On the other hand, if the content of the diamine residues derived from the dimer diamine composition is more than 95 mol% relative to the total diamine residues, the mobility of the molecular chain of the polyimide may be excessively increased, and the dielectric loss tangent may increase.

[0025] The dimer diamine composition is a refined product containing the following component (a) as a main component with the amounts of components (b) and (c) being controlled.

[0026] (a) dimer diamine; The dimer diamine of component (a) is a dimer acid in which the two terminal carboxylic acid groups (-COOH) of the dimer acid are replaced by primary aminomethyl groups (-CH 2 -NH 2 ) or amino group (-NH 2) is substituted. Dimer acid is a known dibasic acid obtained by intermolecular polymerization of unsaturated fatty acids, and its industrial production process is almost standardized in the industry, and is obtained by dimerizing unsaturated fatty acids having 11 to 22 carbon atoms using a clay catalyst or the like. Industrially obtained dimer acid is mainly composed of a dibasic acid having 36 carbon atoms obtained by dimerizing unsaturated fatty acids having 18 carbon atoms, such as oleic acid, linoleic acid, and linolenic acid, but contains any amount of monomer acid (having 18 carbon atoms), trimer acid (having 54 carbon atoms), and other polymerized fatty acids having 20 to 54 carbon atoms depending on the degree of purification. In addition, although double bonds remain after the dimerization reaction, in the present invention, those which have been further subjected to a hydrogenation reaction to reduce the degree of unsaturation are also included in the dimer acid. The dimer diamine of the component (a) can be defined as a diamine compound obtained by substituting the terminal carboxylic acid group of a dibasic acid compound having 18 to 54 carbon atoms, preferably 22 to 44 carbon atoms, with a primary aminomethyl group or an amino group.

[0027] As a feature of dimer diamine, it is possible to impart characteristics derived from the skeleton of dimer acid. That is, since dimer diamine is an aliphatic macromolecule with a molecular weight of about 560 to 620, it is possible to increase the molar volume of the molecule and relatively reduce the polar group of the polyimide. It is considered that such a feature of dimer acid type diamine contributes to improving the dielectric properties by reducing the relative dielectric constant and dielectric loss tangent while suppressing the deterioration of the heat resistance of the polyimide. In addition, since it has two freely moving hydrophobic chains with 7 to 9 carbon atoms and two chain-like aliphatic amino groups with a length close to 18 carbon atoms, it is not only possible to impart flexibility to the polyimide, but also possible to make the polyimide have an asymmetric chemical structure or a non-planar chemical structure, and therefore it is considered that it is possible to reduce the dielectric constant of the polyimide.

[0028] The dimer diamine composition used may be one in which the dimer diamine content of component (a) is increased to 96% by weight or more, preferably 97% by weight or more, more preferably 98% by weight or more by a purification method such as molecular distillation. By increasing the dimer diamine content of component (a) to 96% by weight or more, the broadening of the molecular weight distribution of the polyimide can be suppressed. If technically possible, it is best that the entire dimer diamine composition (100% by weight) is composed of component (a) dimer diamine.

[0029] (b) a monoamine compound obtained by substituting a terminal carboxylic acid group of a monobasic acid compound having 10 to 40 carbon atoms with a primary aminomethyl group or an amino group; The monobasic acid compound having 10 to 40 carbon atoms is a mixture of a monobasic unsaturated fatty acid having 10 to 20 carbon atoms derived from the raw material of dimer acid, and a monobasic acid compound having 21 to 40 carbon atoms which is a by-product during the production of dimer acid. The monoamine compound is obtained by substituting the terminal carboxylic acid group of these monobasic acid compounds with a primary aminomethyl group or an amino group.

[0030] The monoamine compound (b) is a component that suppresses an increase in the molecular weight of the polyimide. During polymerization of the polyamic acid or polyimide, the monofunctional amino group of the monoamine compound reacts with the terminal acid anhydride group of the polyamic acid or polyimide to cap the terminal acid anhydride group, thereby suppressing an increase in the molecular weight of the polyamic acid or polyimide.

[0031] (c) an amine compound obtained by substituting a terminal carboxylic acid group of a polybasic acid compound having a hydrocarbon group having 41 to 80 carbon atoms with a primary aminomethyl group or an amino group (excluding the above-mentioned dimer diamine); The polybasic acid compound having a hydrocarbon group having 41 to 80 carbon atoms is a polybasic acid compound mainly composed of a tribasic acid compound having 41 to 80 carbon atoms, which is a by-product during the production of dimer acid. It may also contain a polymerized fatty acid other than dimer acid having 41 to 80 carbon atoms. The amine compound is obtained by substituting the terminal carboxylic acid group of these polybasic acid compounds with a primary aminomethyl group or an amino group.

[0032] The amine compound (c) is a component that promotes an increase in the molecular weight of the polyimide. The trifunctional or higher amino group, the main component of which is a triamine derived from a trimer acid, reacts with the terminal acid anhydride group of the polyamic acid or polyimide, rapidly increasing the molecular weight of the polyimide. In addition, amine compounds derived from polymerized fatty acids other than dimer acids having 41 to 80 carbon atoms also increase the molecular weight of the polyimide, causing gelation of the polyamic acid or polyimide.

[0033] When each component is quantified by measurement using gel permeation chromatography (GPC), in order to easily confirm the peak start, peak top, and peak end of each component of the dimer diamine composition, a sample of the dimer diamine composition treated with acetic anhydride and pyridine is used, and cyclohexanone is used as an internal standard. Using the sample thus prepared, each component is quantified by the area percentage of the GPC chromatogram. The peak start and peak end of each component are the minimum values ​​of each peak curve, and the area percentage of the chromatogram can be calculated based on this.

[0034] In addition, the dimer diamine composition has a total area percentage of components (b) and (c) of 4% or less, preferably less than 4%, in a chromatogram obtained by GPC measurement. By keeping the total area percentage of components (b) and (c) at 4% or less, the broadening of the molecular weight distribution of the polyimide can be suppressed.

[0035] The area percentage of the chromatogram of the (b) component is preferably 3% or less, more preferably 2% or less, and even more preferably 1% or less. By setting it in such a range, it is possible to suppress the decrease in the molecular weight of the polyimide, and further to widen the range of the molar ratio of the tetracarboxylic dianhydride component and the diamine component. It is not necessary for the (b) component to be contained in the dimer diamine composition.

[0036] The area percentage of the chromatogram of component (c) is 2% or less, preferably 1.8% or less, and more preferably 1.5% or less. By setting it in such a range, a sudden increase in the molecular weight of the polyimide can be suppressed, and further, an increase in the dielectric tangent of the resin film over a wide frequency range can be suppressed. Note that component (c) does not have to be contained in the dimer diamine composition.

[0037] In addition, when the ratio (b / c) of the area percentages of the chromatograms of the components (b) and (c) is 1 or more, the molar ratio of the tetracarboxylic dianhydride component and the diamine component (tetracarboxylic dianhydride component / diamine component) is preferably 0.97 or more and less than 1.0. By setting such a molar ratio, it becomes easier to control the molecular weight of the polyimide.

[0038] Furthermore, when the ratio (b / c) of the area percentages of the components (b) and (c) in the chromatograms is less than 1, the molar ratio of the tetracarboxylic dianhydride component and the diamine component (tetracarboxylic dianhydride component / diamine component) is preferably 0.97 or more and 1.1 or less. By setting such a molar ratio, it becomes easier to control the molecular weight of the polyimide.

[0039] The dimer diamine composition is available as a commercially available product, and is preferably purified to reduce the amount of components other than the dimer diamine of the component (a), for example, the amount of the component (a) is preferably 96% by area or more. The purification method is not particularly limited, but known methods such as distillation and precipitation purification are suitable. Examples of commercially available dimer diamine compositions include PRIAMINE 1073 (trade name), PRIAMINE 1074 (trade name), and PRIAMINE 1075 (trade name) manufactured by Croda Japan.

[0040] The adhesive polyimide also contains, relative to the total diamine residues, a diamine residue derived from a diamine compound (hereinafter sometimes referred to as a "reactive double bond-containing diamine compound") that contains a biphenyl skeleton or a naphthalene skeleton and that has at least one substituent having a carbon-carbon double bond selected from the group consisting of a vinyl group, an acrylic group (acrylate group), a methacrylic group (methacrylate group) and an allyl group, in an amount of 5 mol % or more and 25 mol % or less, preferably 10 mol % or more and 20 mol % or less. By containing the diamine residue derived from the reactive double bond-containing diamine compound within the above range, the adhesive polyimide can have a low dielectric tangent, and the solder heat resistance and flame retardancy are also improved. In addition, by containing a highly reactive double bond, crosslinking is possible, and the introduction of a flame retardant compound into the polyimide skeleton is facilitated, so that the solder heat resistance and flame retardancy can be further improved. If the diamine residue derived from the reactive double bond-containing diamine compound is less than 5 mol%, the effect of improving the dielectric properties, solder heat resistance, and flame retardancy may not be exhibited, and if it exceeds 25 mol%, the reactive double bond-containing diamine compounds are more likely to polymerize with each other, making it difficult to form crosslinks.

[0041] As the reactive double bond-containing diamine compound, for example, a diamine compound represented by the following general formula (1) or (2) can be preferably used. The diamine compounds represented by the general formulas (1) and (2) can increase the aromatic ring concentration of the polyimide due to their basic skeleton and suppress the mobility of the polyimide molecules, thereby contributing to a low dielectric loss tangent.

[0042] [ka] In the general formulas (1) and (2), X independently represents a vinyl group, an acrylic group, a methacrylic group, or an allyl group, and m and n independently represent an integer of 0 to 3, except for the case where m and n are both 0.

[0043] Preferred examples of the reactive double bond-containing diamine compound include 2,2'-divinyl-4,4'-diaminobiphenyl (VAB) and 4,8-divinylnaphthalene-2,6-diamine.

[0044] Other diamine compounds that can be used in polyimides include aromatic diamine compounds. Specific examples of these include 1,4-diaminobenzene (p-PDA; paraphenylenediamine), 2,2'-dimethyl-4,4'-diaminobiphenyl (m-TB), 2,2'-n-propyl-4,4'-diaminobiphenyl (m-NPB), 4-aminophenyl-4'-aminobenzoate (APAB), 2,2-bis-[4-(3-aminophenoxy)phenyl]propane, bis[4-(3-aminophenoxy)phenyl]sulfone, bis[4-(3-aminophenoxy)biphenyl, bis[1-(3-aminophenoxy) ]biphenyl, bis[4-(3-aminophenoxy)phenyl]methane, bis[4-(3-aminophenoxy)phenyl]ether, bis[4-(3-aminophenoxy)]benzophenone, 9,9-bis[4-(3-aminophenoxy)phenyl]fluorene, 2,2-bis-[4-(4-aminophenoxy)phenyl]hexafluoropropane, 2,2-bis-[4-(3-aminophenoxy)phenyl]hexafluoropropane, 3,3'-dimethyl-4,4'-diaminobiphenyl, 4,4'-methylenedi-o-toluidin , 4,4'-methylenedi-2,6-xylidine, 4,4'-methylene-2,6-diethylaniline, 3,3'-diaminodiphenylethane, 3,3'-diaminobiphenyl, 3,3'-dimethoxybenzidine, 3,3''-diamino-p-terphenyl, 4,4'-[1,4-phenylenebis(1-methylethylidene)]bisaniline, 4,4'-[1,3-phenylenebis(1-methylethylidene)]bisaniline, bis(p-aminocyclohexyl)methane, bis(p-β-amino-t-butylphenyl)ether, bis( p-β-methyl-δ-aminopentyl)benzene, p-bis(2-methyl-4-aminopentyl)benzene, p-bis(1,1-dimethyl-5-aminopentyl)benzene, 1,5-diaminonaphthalene, 2,6-diaminonaphthalene, 2,4-bis(β-amino-t-butyl)toluene, 2,4-diaminotoluene, m-xylene-2,5-diamine, p-xylene-2,5-diamine, m-xylylenediamine, p-xylylenediamine, 2,6-diaminopyridine, 2,5-diaminopyridine, 2,5-diamino-1,3,Examples of diamine compounds include 4-oxadiazole, piperazine, 2'-methoxy-4,4'-diaminobenzanilide, 4,4'-diaminobenzanilide, 1,3-bis[2-(4-aminophenyl)-2-propyl]benzene, 6-amino-2-(4-aminophenoxy)benzoxazole, and 1,3-bis(3-aminophenoxy)benzene.

[0045] Polyimide can be produced by reacting the above-mentioned tetracarboxylic anhydride component and diamine component in a solvent to generate polyamic acid, which is then subjected to heating and ring-closing. For example, the tetracarboxylic anhydride component and the diamine component are dissolved in an organic solvent in approximately equimolar amounts, and the mixture is stirred at a temperature in the range of 0 to 100°C for 30 minutes to 24 hours to cause a polymerization reaction, thereby obtaining polyamic acid, which is a precursor of polyimide. In the reaction, the reaction components are dissolved in the organic solvent so that the generated precursor is in the range of 5 to 50% by weight, preferably in the range of 10 to 40% by weight. Examples of organic solvents used in the polymerization reaction include N,N-dimethylformamide (DMF), N,N-dimethylacetamide (DMAc), N,N-diethylacetamide, N-methyl-2-pyrrolidone (NMP), 2-butanone, dimethylsulfoxide (DMSO), hexamethylphosphoramide, N-methylcaprolactam, dimethyl sulfate, cyclohexanone, methylcyclohexane, dioxane, tetrahydrofuran, diglyme, triglyme, methanol, ethanol, benzyl alcohol, and cresol. Two or more of these solvents can be used in combination, and aromatic hydrocarbons such as xylene and toluene can also be used in combination. The amount of such an organic solvent is not particularly limited, but it is preferable to adjust the amount so that the concentration of the polyamic acid solution obtained by the polymerization reaction is about 5 to 50% by weight.

[0046] The synthesized polyamic acid is usually advantageously used as a reaction solvent solution, but can be concentrated, diluted, or replaced with another organic solvent if necessary. Polyamic acid is generally advantageously used because it has excellent solvent solubility. The viscosity of the polyamic acid solution is preferably within the range of 500 cps to 100,000 cps. If it is outside this range, defects such as uneven thickness and streaks are likely to occur in the film during coating operation using a coater or the like.

[0047] The method for imidizing polyamic acid to form polyimide is not particularly limited, and for example, a heat treatment in which the polyamic acid is heated in the above-mentioned solvent at a temperature in the range of 80 to 400° C. for 1 to 24 hours is preferably used. The temperature may be constant, or the temperature may be changed during the process.

[0048] In the adhesive polyimide, the dielectric properties, thermal expansion coefficient, tensile modulus, glass transition temperature, etc. can be controlled by selecting the types of the tetracarboxylic anhydride component and the diamine component, and the molar ratios of the two or more tetracarboxylic anhydride components or diamine components when they are used. In addition, in the adhesive polyimide, when a plurality of polyimide structural units are present, they may be present as blocks or randomly, but it is preferable that they are present randomly.

[0049] The imide group concentration of the adhesive polyimide is preferably 22% by weight or less, more preferably 20% by weight or less. Here, the "imide group concentration" refers to the ratio of the imide group (-(CO) 2 The imide group concentration is calculated by dividing the molecular weight of the imide (-N-) by the molecular weight of the entire polyimide structure. If the imide group concentration exceeds 22% by weight, the molecular weight of the resin itself decreases, and the low moisture absorption property deteriorates due to an increase in polar groups, and Tg and tensile modulus increase.

[0050] The adhesive polyimide is most preferably a completely imidized structure. However, a part of the polyimide may be an amic acid. The imidization rate can be determined by measuring the infrared absorption spectrum of the polyimide thin film by a single reflection ATR method using a Fourier transform infrared spectrophotometer (commercially available: JASCO Corporation, product name: FT / IR620) at 1015 cm -1 Based on the benzene ring absorber near 1780cm -1 It can be calculated from the absorbance of the C=O stretching derived from the imide group.

[0051] [Resin composition] The resin composition according to one embodiment of the present invention comprises the following components (A) and (B): (A) adhesive polyimide; and (B) a crosslinking agent, Contains:

[0052] <Component (A): adhesive polyimide> In the resin composition of the present embodiment, the adhesive polyimide of the component (A) is as described above.

[0053] <Component (B); Crosslinking agent> By including the crosslinking agent of component (B), crosslinking of the adhesive polyimide becomes possible, and the resin film obtained from the resin composition has improved solder heat resistance and flame retardancy, while suppressing bleed-out and reducing the dielectric loss tangent. The crosslinking agent of component (B) that can be blended in the resin composition may be a compound having a functional group in the molecule that can react with a highly reactive substituent having a carbon-carbon double bond in the adhesive polyimide of component (A) to form a crosslink, and examples of such functional groups include vinyl groups, acrylic groups (acrylate groups), methacrylic groups (methacrylate groups), allyl groups, and acryloyl groups. Examples of compounds having such functional groups include 1,5-hexadiene, triallylamine, and dipentaerythritol hexaacrylate. As shown in the examples below, the crosslinking agent of component (B) may also be a compound containing an atom such as phosphorus in the molecule, and in this case, the effect of further improving the flame retardancy of the resin film after crosslinking can be expected.

[0054] The content of the (B) component in the resin composition is preferably in the range of 5 parts by weight to 30 parts by weight, more preferably in the range of 10 parts by weight to 25 parts by weight, relative to 100 parts by weight of the (A) component. If the content of the (B) component is less than 5 parts by weight, crosslinking does not proceed sufficiently, making it difficult to improve solder heat resistance, low dielectric tangent, and flame retardancy. If the content of the (B) component is more than 30 parts by weight, unreacted crosslinking agent may cause bleeding out, adhesion may decrease when a resin film is formed, and the (B) components may react with each other, resulting in decreased handleability.

[0055] The crosslinking between component (A) and component (B) is carried out by reacting a substituent having a carbon-carbon double bond in the adhesive polyimide of component (A) with a functional group contained in the crosslinking agent of component (B). For example, this can be achieved by a method such as (i) synthesis of an adhesive polyimide (imidization), followed by addition of a crosslinking agent for component (B) and heating, or (ii) processing a resin composition containing components (A) and (B) into a predetermined shape (for example, after coating on a substrate or forming into a film) and then heating. The reaction conditions for crosslinking are not particularly limited, but may be, for example, a method of heating to a temperature within the range of 100 to 220° C., preferably within the range of 120 to 200° C. The reaction time is preferably about 30 minutes to 24 hours. In order to hasten the start of the reaction, a polymerization initiator of the component (D) described below may be used as necessary.

[0056] <Component (C): Elastomer resin> The resin composition may further contain an elastomer resin as component (C). By blending the elastomer resin as component (C), the toughness of the resin film can be increased, and sufficient peel strength and low dielectric tangent can be maintained. The elastomer resin as component (C) is preferably a copolymer of styrene or a derivative thereof with a conjugated diene compound, and includes a hydrogenated product thereof. Here, examples of styrene or a derivative thereof include, but are not limited to, styrene, methylstyrene, butylstyrene, divinylbenzene, vinyltoluene, etc. Furthermore, examples of conjugated diene compounds include, but are not limited to, butadiene, isoprene, 1,3-pentadiene, etc. In addition, the elastomer resin is preferably hydrogenated, which further improves the thermal stability and makes it less susceptible to deterioration such as decomposition and polymerization, and also enhances the aliphatic properties and improves compatibility with the adhesive polyimide.

[0057] The copolymer structure of the elastomer resin of component (C) may be a block structure or a random structure. Preferred examples of the elastomer resin include styrene-butadiene-styrene block copolymer (SBS), styrene-butadiene-butylene-styrene block copolymer (SBBS), styrene-ethylene-butylene-styrene block copolymer (SEBS), styrene-ethylene-propylene-styrene block copolymer (SEPS), and styrene-ethylene-ethylene-propylene-styrene block copolymer (SEEPS), but are not limited thereto.

[0058] The acid value of the elastomer resin of the component (C) is 10 mgKOH / g or less, preferably 1 mgKOH / g or less, and more preferably 0 mgKOH / g. By blending an elastomer resin with an acid value of 10 mgKOH / g or less in the resin composition, the dielectric tangent when a resin film is formed can be reduced and good peel strength can be maintained. On the other hand, if the acid value exceeds 10 mgKOH / g, the dielectric properties deteriorate due to an increase in polar groups, and the compatibility with the component (A) deteriorates, resulting in a decrease in adhesion when a resin film is formed. Therefore, the lower the acid value, the better, and a non-acid-modified one (i.e., an acid value of 0 mgKOH / g) is most suitable as the component (C) of the present invention. In the present invention, when the adhesive polyimide contains a residue derived from dimer diamine, it is possible to develop excellent adhesion, so that even if a non-acid-modified (i.e., a highly aliphatic) elastomer resin is used, a decrease in adhesive strength can be avoided.

[0059] The elastomer resin of component (C) contains a styrene unit [-CH 2 CH(C 6 H 5 The content of styrene units in the elastomer resin is preferably in the range of 10% by weight to 65% by weight, more preferably in the range of 20% by weight to 65% by weight, and most preferably in the range of 30% by weight to 60% by weight. If the content of styrene units in the elastomer resin is less than 10% by weight, the elastic modulus of the resin decreases and the handling properties as a film deteriorate, whereas if it exceeds 65% by weight, the resin becomes rigid and difficult to use as an adhesive, and the rubber component in the elastomer resin decreases, leading to deterioration of the dielectric properties. In addition, by having the content ratio of styrene units within the above range, the proportion of aromatic rings in the resin film is increased, so that when via holes (through holes) and blind via holes are formed by laser processing in the process of manufacturing a circuit board using the resin film, it is possible to increase the absorbency in the ultraviolet region and further improve the laser processability.

[0060] The weight average molecular weight of the elastomer resin of component (C) is, for example, preferably within the range of 50,000 to 300,000, and more preferably within the range of 80,000 to 270,000. If the weight average molecular weight of component (C) is lower than the above range, the effect of improving the peel strength and dielectric properties may be reduced, whereas if it is higher, the viscosity of the resin composition may be high, making it difficult to produce a resin film.

[0061] As the elastomer resin of the component (C), a commercially available product can be appropriately selected and used as long as the acid value is 10 mgKOH / g or less. As such a commercially available elastomer resin, for example, A1535HU (trade name), G1652MU (trade name), G1726VS (trade name), G1645VS (trade name), FG1901GT (trade name), G1650MU (trade name), G1654HU (trade name), G1730VO (trade name), MD1653MO (trade name), etc. manufactured by KRATON can be preferably used.

[0062] The content of the (C) component in the resin composition relative to 100 parts by weight of the (A) component is in the range of 5 parts by weight to 100 parts by weight, preferably 10 parts by weight to 90 parts by weight, and more preferably 20 parts by weight to 80 parts by weight. If the content of the (C) component relative to 100 parts by weight of the (A) component is less than 5 parts by weight, the peel strength may not be sufficiently exhibited. On the other hand, if the weight ratio of the (C) component exceeds 100 parts by weight, the adhesiveness when the resin film is formed may decrease, and the solid content concentration in the resin composition may become too high, increasing the viscosity and decreasing the handleability.

[0063] <Component (D): Polymerization initiator> The resin composition may further contain a polymerization initiator as component (D). As the polymerization initiator of component (D), any one generally used as a radical polymerization initiator may be used without any particular limitation, but preferred examples include dihalogen compounds, azo compounds, and organic peroxides. Among these, organic peroxides are preferred. As the polymerization initiator of component (D), a commercially available product may be appropriately selected and used. As such a commercially available polymerization initiator, for example, Perbutyl (registered trademark) P (manufactured by NOF Corporation), Perbutyl (registered trademark) C (manufactured by NOF Corporation), etc. are preferred.

[0064] The content of the (D) component in the resin composition is preferably within the range of 0.5 parts by weight to 2.0 parts by weight per 100 parts by weight of the (A) component. If the content of the (D) component is less than 0.5 parts by weight per 100 parts by weight of the (A) component, the effect of adding the polymerization initiator may not be fully exhibited. On the other hand, if the weight ratio of the (D) component exceeds 2.0 parts by weight, the dielectric loss tangent may deteriorate and the storage stability and handling properties of the resin composition may decrease.

[0065] In addition, as a method for curing the adhesive polyimide, it is also possible to mix and cure it with, for example, an epoxy resin, an epoxy resin curing agent, or a compound having an unsaturated bond such as maleimide, activated ester resin, or a resin having a styrene skeleton.

[0066] Furthermore, the resin composition of the present embodiment may contain a solvent such as an organic solvent. Since the adhesive polyimide has solvent solubility, the resin composition of the present embodiment may be prepared as a polyimide solution (varnish) containing a solvent. As the organic solvent, it is preferable to use a mixed solvent in which one or more selected from N,N-dimethylformamide (DMF), N,N-dimethylacetamide (DMAc), N,N-diethylacetamide, N-methyl-2-pyrrolidone (NMP), 2-butanone, dimethylsulfoxide (DMSO), hexamethylphosphoramide, N-methylcaprolactam, dimethyl sulfate, cyclohexanone, dioxane, tetrahydrofuran, diglyme, triglyme, cresol, etc. are mixed with the aromatic hydrocarbon solvent in any ratio. The content of the solvent is not particularly limited, but it is preferable to adjust the amount used so that the concentration of the polyamic acid or polyimide becomes about 5 to 30% by weight.

[0067] The resin composition of the present embodiment may further contain, as necessary, optional components such as inorganic fillers, organic fillers, plasticizers, curing accelerators, coupling agents, pigments, and flame retardants, within the scope of the invention. Examples of inorganic fillers include silicon dioxide, aluminum oxide, beryllium oxide, niobium oxide, titanium oxide, magnesium oxide, boron nitride, aluminum nitride, silicon nitride, aluminum fluoride, calcium fluoride, magnesium fluoride, potassium silicofluoride, and metal phosphinates. These may be used alone or in combination of two or more. Other resin components such as epoxy resins, fluororesins, and olefin-based resins may also be used as optional components.

[0068] [viscosity] The viscosity of the resin composition is preferably within a range of, for example, 3000 cps to 100000 cps, more preferably 5000 cps to 50000 cps, so as to improve the handling property when applying the resin composition and to easily form a coating film of uniform thickness. If the viscosity is outside the above range, defects such as uneven thickness and streaks are likely to occur in the film during application by a coater or the like.

[0069] [Preparation of resin composition] The resin composition can be prepared, for example, by blending and mixing the (B) component and, if necessary, the (C) and (D) components into a resin solution of the adhesive polyimide (A) component prepared using any solvent. In order to mix uniformly, the (B), (C) and (D) components may be mixed in a state of being dissolved in a solvent, or a solvent that has high solubility in the (B), (C) and (D) components may be added.

[0070] The resin composition of the present embodiment has excellent flexibility and thermoplasticity when used to form an adhesive layer, and therefore has favorable properties for applications such as adhesive layer materials and coverlay film adhesives for protecting wiring parts in, for example, FPCs and rigid-flex circuit boards.

[0071] [Resin film] The resin film of the present embodiment is a resin film consisting of a single layer or multiple layers including a polyimide layer, and the polyimide layer is formed by forming the adhesive polyimide or the solid content (the remainder excluding the solvent) of the above-mentioned resin composition into a film as a main component. The resin film of the present embodiment has excellent high-frequency characteristics, as well as sufficient adhesiveness (especially peel strength), solder heat resistance, and flame retardancy for practical use.

[0072] The resin film of the present embodiment is not particularly limited as long as it is an insulating resin film containing the above-mentioned thermoplastic resin layer, and may be a film (sheet) consisting of insulating resin only, or may be an insulating resin film laminated on a substrate such as a resin sheet, such as copper foil, a glass plate, a polyimide film, a polyamide film, or a polyester film.

[0073] (Dielectric constant) In order to ensure impedance matching when used in a circuit board such as an FPC and to reduce loss of an electric signal, the resin film of the present embodiment has a relative dielectric constant (ε) at 10 GHz measured by a split post dielectric resonator (SPDR) after 24 hours of humidity control under constant temperature and humidity conditions (normal state) of 23° C. and 50% RH, of preferably 3.3 or less, more preferably 3.1 or less. If the relative dielectric constant exceeds 3.3, problems such as loss of an electric signal are likely to occur on the transmission path of a high-frequency signal when used in a circuit board such as an FPC.

[0074] (Dielectric tangent) In addition, in order to reduce loss of electrical signals when the resin film of the present embodiment is used in a circuit board such as an FPC, the dielectric loss tangent (Tan δ) at 10 GHz measured by a split post dielectric resonator (SPDR) after 24 hours of humidity control under constant temperature and humidity conditions (normal state) of 23° C. and 50% RH is preferably less than 0.002, more preferably 0.0017 or less. If the dielectric loss tangent is 0.0020 or more, problems such as loss of electrical signals are likely to occur on the transmission path of high frequency signals when the resin film is used in a circuit board such as an FPC.

[0075] (glass transition temperature) The resin film of the present embodiment preferably has a glass transition temperature (Tg) of 250° C. or less, and more preferably in the range of 40° C. to 200° C. If the resin film has a Tg of 250° C. or less, thermocompression bonding at a low temperature is possible, and the internal stress generated during lamination can be alleviated, and dimensional change after circuit processing can be suppressed. If the resin film has a Tg of more than 250° C., the bonding temperature becomes high, and there is a risk of impairing dimensional stability after circuit processing.

[0076] (Thickness) The thickness of the resin film of the present embodiment is preferably, for example, in the range of 5 μm to 125 μm, and more preferably in the range of 8 μm to 100 μm. If the thickness of the resin film is less than 5 μm, there is a risk of problems such as wrinkles occurring during transportation in the production of the resin film, while if the thickness of the resin film exceeds 125 μm, there is a risk of a decrease in productivity of the resin film.

[0077] (tensile modulus) The resin film of the present embodiment preferably has a tensile modulus in the range of 0.1 GPa to 3.0 GPa, more preferably in the range of 0.2 GPa to 2.0 GPa, from the viewpoints of reducing wrinkles, preventing air bubbles from being trapped during lamination, and handling properties.

[0078] (Maximum elongation) The resin film of the present embodiment preferably has a maximum elongation within the range of 30% to 250%, more preferably within the range of 100% to 200%, from the viewpoints of foldability and crack prevention when applied as an insulating resin layer of an FPC.

[0079] Since the resin film of the present embodiment has a low dielectric tangent and excellent adhesion, it is useful as an adhesive layer in a coverlay film, an adhesive layer in a circuit board, a multilayer circuit board, a resin-coated copper foil, a bond ply, a bonding sheet, and the like.

[0080] (solder heat resistance) The resin film of this embodiment preferably has a solder heat resistance (dry) of 280° C. or more, and a solder heat resistance (moisture absorption) of 260° C. or more, as measured by the test method and conditions shown in the Examples below. If swelling occurs at the temperature during solder reflow, wiring misalignment and poor conduction will occur, so by having a solder heat resistance (dry, moisture absorption) of the above temperature or more, it is possible to increase the yield in the mounting process and improve the reliability of electronic components. Until now, when evaluated without performing pretreatment such as prior drying, an adhesive film with high solder heat resistance and low dielectric tangent has not been obtained, so there is a demand for one with high solder heat resistance without pretreatment, and the resin film of this embodiment can satisfy such required characteristics.

[0081] (Peel strength) The resin film of the present embodiment preferably has a peel strength of 1.0 kN / m or more, measured by the test method and conditions shown in the Examples below. By having a peel strength of 1.0 kN / m or more, sufficient adhesion for practical use can be obtained between the wiring layer and the resin layer after circuit processing.

[0082] [Laminate] The laminate according to one embodiment of the present invention has a substrate and an adhesive layer laminated on at least one surface of the substrate, the adhesive layer being made of the above-mentioned resin film. The laminate may also include any layer other than the above. Examples of the substrate in the laminate include substrates made of inorganic materials such as copper foil and glass plate, and substrates made of resin materials such as polyimide film, polyamide film, and polyester film. Preferred embodiments of the laminate include a coverlay film and a resin-coated copper foil.

[0083] [Coverlay film] The coverlay film, which is one embodiment of the laminate, has a coverlay film material layer as a substrate and an adhesive layer laminated on one side of the coverlay film material layer, the adhesive layer being made of the above-mentioned resin film. Note that the coverlay film may include any layer other than those described above.

[0084] The material of the coverlay film material layer is not particularly limited, but for example, polyimide-based films such as polyimide resins, polyetherimide resins, and polyamideimide resins, polyamide-based films, and polyester-based films can be used. Among these, it is preferable to use polyimide-based films with excellent heat resistance. In addition, the coverlay film material can contain a black pigment in order to effectively exhibit light-shielding properties, concealing properties, design properties, and the like, and can also contain optional components such as matte pigments that suppress the gloss of the surface, within a range that does not impair the effect of improving the dielectric properties.

[0085] The thickness of the coverlay film material layer is not particularly limited, but is preferably within the range of, for example, 5 μm or more and 100 μm or less. The thickness of the adhesive layer is not particularly limited, but is preferably within the range of, for example, 10 μm to 75 μm.

[0086] The coverlay film of the present embodiment can be produced by the method exemplified below. First, as a first method, a varnish-like resin composition containing a solvent is applied to one side of a film material layer for a coverlay, and then the composition is dried at a temperature of, for example, 80 to 180°C to form an adhesive layer, thereby forming a coverlay film having a film material layer for a coverlay and an adhesive layer.

[0087] As a second method, a varnish-like resin composition containing a solvent is applied onto any substrate, dried at a temperature of, for example, 80 to 180°C, and then peeled off to form a resin film for the adhesive layer. This resin film is then thermocompressed to a film material layer for the coverlay at a temperature of, for example, 60 to 220°C to form a coverlay film.

[0088] [Copper foil with resin] The resin-coated copper foil, which is another embodiment of the laminate, is obtained by laminating an adhesive layer on at least one side of a copper foil as a base material, and the adhesive layer is made of the above-mentioned resin film. Note that the resin-coated copper foil of this embodiment may include any layer other than the above.

[0089] The thickness of the adhesive layer in the resin-coated copper foil is preferably within the range of 2 to 125 μm, and more preferably within the range of 2 to 100 μm. If the thickness of the adhesive layer is less than the lower limit, problems such as insufficient adhesion may occur. On the other hand, if the thickness of the adhesive layer exceeds the upper limit, problems such as reduced dimensional stability may occur. In addition, from the viewpoint of lowering the dielectric constant and the dielectric loss tangent, the thickness of the adhesive layer is preferably 3 μm or more.

[0090] The material of the copper foil in the resin-coated copper foil is preferably one mainly composed of copper or a copper alloy. The thickness of the copper foil is preferably 35 μm or less, more preferably in the range of 5 to 25 μm. From the viewpoint of production stability and handling, the lower limit of the thickness of the copper foil is preferably 5 μm. The copper foil may be a rolled copper foil or an electrolytic copper foil. In addition, a commercially available copper foil can be used as the copper foil.

[0091] The resin-attached copper foil may be prepared, for example, by forming a seed layer by sputtering a metal on a resin film, and then forming a copper layer by, for example, copper plating, or by laminating a resin film and a copper foil by a method such as thermocompression bonding. Furthermore, the resin-attached copper foil may be prepared by casting a coating solution of a resin composition to form an adhesive layer on the copper foil, drying the coating film, and then carrying out a required heat treatment.

[0092] [Metal-clad laminate] (First aspect) The metal-clad laminate according to one embodiment of the present invention includes an insulating resin layer and a metal layer laminated on at least one surface of the insulating resin layer, at least one of the insulating resin layers being made of the above-mentioned resin film. Note that the metal-clad laminate according to this embodiment may include any layer other than those described above.

[0093] (Second aspect) The metal-clad laminate according to another embodiment of the present invention is a so-called three-layer metal-clad laminate, which includes, for example, an insulating resin layer, an adhesive layer laminated on at least one side of the insulating resin layer, and a metal layer laminated on the insulating resin layer via the adhesive layer, and the adhesive layer is made of the above-mentioned resin film. The three-layer metal-clad laminate may include any layer other than the above. The three-layer metal-clad laminate may have an adhesive layer on one or both sides of the insulating resin layer, and the metal layer may be provided on one or both sides of the insulating resin layer via the adhesive layer. In other words, the three-layer metal-clad laminate may be a single-sided metal-clad laminate or a double-sided metal-clad laminate. A single-sided or double-sided FPC can be manufactured by processing the wiring circuit by etching the metal layer of the three-layer metal-clad laminate.

[0094] The insulating resin layer in the three-layer metal-clad laminate is not particularly limited as long as it is made of a resin having electrical insulation properties, and examples thereof include polyimide, epoxy resin, phenolic resin, polyethylene, polypropylene, polytetrafluoroethylene, silicone, ETFE, etc., but is preferably made of polyimide. The polyimide layer constituting the insulating resin layer may be a single layer or multiple layers, but preferably includes a non-thermoplastic polyimide layer.

[0095] The thickness of the insulating resin layer in the three-layer metal-clad laminate is, for example, preferably in the range of 1 to 125 μm, more preferably in the range of 5 to 100 μm. If the thickness of the insulating resin layer is less than the lower limit, problems such as insufficient electrical insulation may occur. On the other hand, if the thickness of the insulating resin layer exceeds the upper limit, problems such as the metal-clad laminate being more likely to warp may occur.

[0096] The thickness of the adhesive layer in the three-layer metal-clad laminate is preferably, for example, within the range of 0.1 to 125 μm, and more preferably within the range of 0.3 to 100 μm. In the three-layer metal-clad laminate of the present embodiment, if the thickness of the adhesive layer is less than the above lower limit, problems such as insufficient adhesion may occur. On the other hand, if the thickness of the adhesive layer exceeds the above upper limit, problems such as reduced dimensional stability may occur. In addition, from the viewpoint of reducing the dielectric constant and dielectric loss tangent of the entire insulating layer, which is a laminate of an insulating resin layer and an adhesive layer, the thickness of the adhesive layer is preferably 3 μm or more. The ratio of the thickness of the insulating resin layer to the thickness of the adhesive layer (thickness of the insulating resin layer / thickness of the adhesive layer) is preferably within a range of, for example, 0.1 to 3.0, and more preferably within a range of 0.15 to 2.0. By setting such a ratio, it is possible to suppress warping of the three-layer metal-clad laminate. Furthermore, the insulating resin layer may contain a filler as necessary. Examples of the filler include silicon dioxide, aluminum oxide, magnesium oxide, beryllium oxide, boron nitride, aluminum nitride, silicon nitride, aluminum fluoride, calcium fluoride, and metal salts of organic phosphinic acid. These can be used alone or in combination of two or more.

[0097] [Circuit board] The circuit board according to the embodiment of the present invention is obtained by wiring the metal layer of the metal-clad laminate according to any of the above embodiments. One or more metal layers of the metal-clad laminate are patterned by a conventional method to form a wiring layer (conductor circuit layer), thereby manufacturing a circuit board such as an FPC. The circuit board may include a coverlay film that covers the wiring layer. EXAMPLES

[0098] The features of the present invention will be described in more detail below with reference to examples. However, the scope of the present invention is not limited to the examples. In the following examples, various measurements and evaluations are as follows, unless otherwise specified.

[0099] [Measurement of weight average molecular weight (Mw) of polyimide] The weight average molecular weight was measured by gel permeation chromatography (manufactured by Tosoh Corporation, product name: HLC-8220GPC was used). Polystyrene was used as a standard substance, and tetrahydrofuran (THF) was used as a developing solvent.

[0100] [Hydroxyl equivalent] The measurement was performed in accordance with JIS K 0070. Specifically, a potentiometric titrator was used, 1,4-dioxane was used as the solvent, acetylation was performed with 1.5 mol / L acetyl chloride, excess acetyl chloride was decomposed with water, and titration was performed with 0.5 mol / L potassium hydroxide.

[0101] [Phosphorus content] Sulfuric acid, hydrochloric acid, and perchloric acid were added to the sample, which was then heated and wet-ashed to convert all phosphorus atoms into orthophosphate. Metavanadate and molybdate were reacted in the sulfuric acid solution, and the absorbance of the resulting phosphorus vanadate molybdate complex was measured at 420 nm. The phosphorus atom content was calculated using a calibration curve prepared in advance using potassium dihydrogen phosphate and expressed as a percentage.

[0102] [Field desorption mass spectrometry (FD-MS)] Molecular weight measurements were performed using a JEOL JMS-T100GCV.

[0103] [Measurement of storage modulus] Measurements were performed using a dynamic viscoelasticity measuring device (DMA: manufactured by TA Instruments, product name: RSA-G2). Storage modulus at 30℃ is 1.0×10 9 Pa or more, and the storage modulus at 280°C is 3.0×10 8 Polyimides with a storage modulus of 1.0×10 Pa or more at 30°C are considered to be "non-thermoplastic polyimides". 8 Pa or more, and the storage modulus at 280°C is 3.0×10 7 Polyimides with a compressive strength of less than 1 Pa were classified as "thermoplastic polyimides."

[0104] [Evaluation of dielectric properties] The polyimide film (cured polyimide film) was left for 24 hours under the conditions of temperature: 23°C and humidity: 50% RH, and then the relative dielectric constant (ε) and dielectric loss tangent (Tan δ) at a frequency of 10 GHz were measured using a vector network analyzer (manufactured by Agilent, product name: Vector Network Analyzer E8363C) and an SPDR resonator.

[0105] [Glass transition temperature (Tg)] The adhesive sheet was pressed under the conditions of temperature: 160°C, pressure: 3.5MPa, and time: 60 minutes, and then cut into test pieces measuring 5mm x 20mm. Measurements were performed using a dynamic viscoelasticity measuring device (DMA: manufactured by TA Instruments, product name: RSA-G2) at a heating rate of 4°C / min from 30°C to 200°C and a frequency of 11Hz. The temperature at which the change in elastic modulus (tan δ) was maximum was determined as the glass transition temperature.

[0106] [Tensile modulus and maximum elongation] Using a tension tester (Tensilon manufactured by Orientec), a tensile test was carried out at 50 mm / min on a resin film test piece (width: 12.7 mm, length: 127 mm) to determine the tensile modulus and maximum elongation at 25°C.

[0107] [Solder heat resistance test (dry)] One side of the copper foil of a double-sided copper-clad laminate (manufactured by Nippon Steel Chemical & Material Co., Ltd., product name: Espanex MB12-25-12UEG) was etched away, and the other copper foil surface and adhesive sheet were laminated by sandwiching them between the copper foils, and pressed under the following conditions: temperature: 160°C, pressure: 3.5MPa, time: 60 minutes. The test piece with the copper foil was dried at 135°C / 60 minutes, and then immersed for 10 seconds in a solder bath set at each evaluation temperature from 260°C to 300°C in 10°C increments, and the adhesion state was observed to confirm the presence or absence of defects such as foaming, swelling, and peeling. The evaluation was made as ◯ (good) when no defects were observed at 280°C, and × (bad) when defects were observed.

[0108] [Solder heat resistance test (moisture absorption)] The copper foil on one side of a double-sided copper-clad laminate (manufactured by Nippon Steel Chemical & Material Co., Ltd., product name: Espanex MB12-25-12UEG) was etched away, and the other copper foil surface and adhesive sheet were laminated by sandwiching them between the copper foils, and pressed under the conditions of temperature: 160°C, pressure: 3.5MPa, and time: 60 minutes. The test piece with the copper foil was left at 40°C and relative humidity: 90%RH for 72 hours, and then immersed for 10 seconds in a solder bath set at each evaluation temperature from 240°C to 300°C in 10°C increments, and the adhesion state was observed to confirm the presence or absence of defects such as foaming, swelling, and peeling. The evaluation was made as ◯ (good) when no defects were observed at 260°C, and × (bad) when defects were observed.

[0109] [Peel strength measurement] A double-sided copper-clad laminate (manufactured by Nippon Steel Chemical & Material Co., Ltd., product name: Espanex MB12-25-12UEG) was cut to a width of 50 mm and a length of 100 mm, and the copper foil on one side of the sample was etched away to place the adhesive sheet to be tested on the copper foil side. A polyimide film (manufactured by Toray DuPont Co., Ltd., product name: Kapton 50EN-S) was then laminated on top of the adhesive sheet and pressed at a temperature of 160°C, a pressure of 3.5 MPa, and a time of 60 minutes to prepare a laminate. This laminate was cut to a width of 5 mm to prepare a test piece, and the peel strength between the adhesive sheet and the copper foil was measured using a tensile tester (manufactured by Toyo Seiki Seisakusho, product name: Strograph VE) when the test piece was pulled in the 180° direction at a speed of 50 mm / min, and this was taken as the peel strength.

[0110] [Film retention evaluation method] The adhesive sheet was cut into a test piece 20 mm wide and 20 mm long, folded along the diagonal to create a crease, and then opened to observe the condition of the film. If the test piece had no cracks even after the crease was created and opened, it was rated as "good," and if there was even a partial crack, it was rated as "no good."

[0111] [Flame retardancy evaluation method] Flame retardancy was evaluated by the following method. Two resin films were laminated to a thickness of 50 μm, and polyimide films (manufactured by Toray DuPont Co., Ltd., product name: Kapton 50EN-S) were laminated on both sides of the film, and pressed under the conditions of temperature: 160°C, pressure: 3.5 MPa, and time: 60 minutes. A sample was cut to 200 ± 5 mm × 50 ± 1 mm, rolled into a cylindrical shape with a diameter of approximately 12.7 mm and a length of 200 ± 5 mm, and a flammability test was performed according to the UL94VTM standard. If the time until the flame went out was within 11 seconds, it was judged as "○" (good), and if it exceeded 11 seconds, it was judged as "×" (bad).

[0112] [Method for measuring amine value] Approximately 2 g of the dimer diamine composition is weighed into a 200-250 mL Erlenmeyer flask, and phenolphthalein is used as an indicator. A 0.1 mol / L ethanolic potassium hydroxide solution is dropped into the solution until the solution turns light pink, and the solution is dissolved in approximately 100 mL of neutralized butanol. 3-7 drops of phenolphthalein solution are added thereto, and titration is performed with 0.1 mol / L ethanolic potassium hydroxide solution while stirring until the sample solution turns light pink. Five drops of bromophenol blue solution are added thereto, and titration is performed with 0.2 mol / L hydrochloric acid / isopropanol solution while stirring until the sample solution turns yellow. The amine value is calculated according to the following formula (1). Amine value = {(V 2 ×C 2 )-(V 1 ×C 1 )}×M KOH / m (1) Here, the amine value is expressed as mg-KOH / g, and M KOH is the molecular weight of potassium hydroxide, 56.1. V and C are the volume and concentration of the solution used in the titration, respectively, and the subscripts 1 and 2 represent a 0.1 mol / L ethanolic potassium hydroxide solution and a 0.2 mol / L hydrochloric acid / isopropanol solution, respectively. Furthermore, m is the sample weight in grams.

[0113] [Calculation of GPC and chromatogram area percentage] (a) Dimer diamine (b) A monoamine compound obtained by substituting the terminal carboxylic acid group of a monobasic acid compound having 10 to 40 carbon atoms with a primary aminomethyl group or an amino group. (c) Amine compounds obtained by substituting the terminal carboxylic acid group of a polybasic acid compound having a hydrocarbon group having 41 to 80 carbon atoms with a primary aminomethyl group or an amino group (excluding the above-mentioned dimer diamine).

[0114] For GPC, 20 mg of the dimer diamine composition was pretreated with 200 μL of acetic anhydride, 200 μL of pyridine, and 2 mL of THF to prepare a 100 mg solution, which was then diluted with 10 mL of THF (containing 1000 ppm of cyclohexanone) to prepare a sample. The prepared sample was measured using a Tosoh Corporation product name: HLC-8220GPC under the following conditions: column: TSK-gel G2000HXL, G1000HXL, flow rate: 1 mL / min, column (oven) temperature: 40° C., injection volume: 50 μL. Cyclohexanone was used as a standard substance to correct the elution time.

[0115] In this case, the retention times were adjusted so that the peak top of the cyclohexanone main peak was at a retention time of 27 to 31 minutes, and the period from the peak start to the peak end of the cyclohexanone main peak was 2 minutes, and the peak top of the main peak excluding the cyclohexanone peak was at a retention time of 18 to 19 minutes, and the period from the peak start to the peak end of the main peak excluding the cyclohexanone peak was 2 minutes to 4 minutes 30 seconds. (a) Component represented by the main peak; (b) A component represented by a GPC peak detected at a time later than the minimum retention time of the main peak; (c) Components represented by GPC peaks detected at earlier retention times than the minimum value of the main peak on the earlier side; was detected.

[0116] The abbreviations used in the examples represent the following compounds. BTDA: 3,3',4,4'-benzophenonetetracarboxylic dianhydride VAB: 2,2'-divinyl-4,4'-diaminobiphenyl DDA: Manufactured by Croda Japan Co., Ltd.; product name: PRIAMINE 1075, distilled and purified (component a: 99.2%, component b: 0%, component c: 0.8%, amine value: 210 mg KOH / g) N-12: Dodecanedioic acid dihydrazide NMP: N-methyl-2-pyrrolidone 6FDA: 4,4'-(hexafluoroisopropylidene)diphthalic anhydride BPDA: 3,3',4,4'-biphenyltetracarboxylic dianhydride Elastomer resin 1: KRATON, product name: A1535HU (hydrogenated polystyrene elastomer resin, styrene unit content: 58% by weight, specific gravity: 0.96, no acid value) In the above DDA, the "%" of component a, component b, and component c means the area percentage of the chromatogram in GPC measurement. The molecular weight of DDA was calculated by the following formula (1). Molecular weight = 56.1 × 2 × 1000 / amine value (1)

[0117] (Synthesis Example 1) <Preparation of phosphorus-containing phenol (phosphorus compound A)> A 2-liter, four-neck flask equipped with a stirrer, a thermometer, and a hydrochloric acid recovery device (a condenser connected to a water scrubber) was charged with 1,500 g of phosphorus oxychloride, 471 g of phenol, and 1.2 g of magnesium chloride as a catalyst.

[0118] The resulting mixed solution was gradually heated to 90°C over about 3 hours while stirring to react, and the generated hydrogen chloride (hydrochloric acid gas) was collected with a water scrubber. Thereafter, the pressure in the flask was gradually reduced to 12 kPa at 120°C to remove unreacted phosphorus oxychloride and phenol, and hydrogen chloride produced as a by-product, yielding 1,055 g of monophenyl phosphorodichloridate (MPC).

[0119] A 2-liter four-neck flask equipped with a stirrer, a thermometer, a dropping funnel, and a condenser was charged with 822 g of 2,3,5-trimethylhydroquinone, 6.3 g of aluminum chloride as a catalyst, and 1,000 g of 1,2-dichlorobenzene as a solvent. The dropping funnel was charged with 570 g of the above MPC.

[0120] The mixed solution in the four-neck flask was heated to 110°C while stirring, and while maintaining the same temperature (110°C), MPC in the dropping funnel was added dropwise over 2 hours. After the dropwise addition, the mixture was gradually heated to 160°C and stirred for 4 hours to obtain a reaction product. The mixture was then cooled to 105°C, and the pressure in the flask was gradually reduced to 6.3kPa to remove the by-product hydrogen chloride.

[0121] The reaction product obtained was washed with dilute hydrochloric acid and water, neutralized and washed with an aqueous sodium carbonate solution, and washed again with water. It was then heated to 150°C and reduced in pressure to 1 kPa to recover water and 1,2-dichlorobenzene. It was further subjected to steam distillation at 110°C under reduced pressure of 1 kPa to remove low boiling points, and cooled to room temperature to obtain 1195 g of a phosphorus-containing phenolic compound (phosphorus compound A) as a black-brown solid. The phosphorus content of the resulting mixture of phosphorus compound A was 6.5%, and the hydroxyl equivalent was 272 g / eq.

[0122] (Synthesis Example 2) <Preparation of phosphorus-containing vinylbenzyl ether compound (phosphorus compound B)> In a glass separable flask equipped with a stirrer, a thermometer, and a cooling tube, 200.0 g of phosphorus compound A and 133.2 g of diethylene glycol dimethyl ether were charged and dissolved in a nitrogen atmosphere at 75°C. 134.0 g of CMS-P (trade name, manufactured by AGC Seimi Chemical Co., Ltd.) was added, and after the mixture became homogenous, 10.0 g of tetrabutylammonium bromide and 222.4 g of a 50% aqueous potassium carbonate solution were added and reacted for 10 hours.

[0123] The reaction solution was then concentrated and dissolved in 674.4 g of toluene, after which the reaction solution was neutralized with a 10% aqueous solution of sodium dihydrogen phosphate and washed with water. The solution was then dehydrated, filtered, and the solvent was concentrated to obtain 340.0 g of a toluene solution of a phosphorus-containing vinylbenzyl ether compound (phosphorus compound B). The obtained phosphorus compound B was analyzed by FD-MS, and a peak at molecular weight 674 was confirmed, confirming that the compound of the following structure was the main component. The phosphorus content was 4.7%.

[0124] [ka]

[0125] (Synthesis Example 3) <Preparation of phosphorus-containing methacryloyl compound (phosphorus compound C)> In a glass separable flask equipped with a stirrer, a thermometer, a condenser, and a dropping funnel, 200.0 g of phosphorus compound A, 133.2 g of tetrahydrofuran, and 104.0 g of triethylamine were charged and dissolved, and then cooled in an ice bath to below 5° C. In a nitrogen atmosphere, 89.6 g of methacryloyl chloride was added dropwise over 1 hour, and the reaction was continued for another 2 hours.

[0126] The reaction solution was then concentrated and dissolved in 608.0 g of toluene, and washed in this order with hydrochloric acid, an aqueous sodium carbonate solution, and water. After washing with water, the solution was dehydrated, filtered, and the solvent was further concentrated to obtain 212.64 g of a toluene solution of a phosphorus-containing methacryloyl compound (phosphorus compound C). The obtained phosphorus compound C was analyzed by FD-MS, and a peak at a molecular weight of 578 was confirmed, confirming that the compound of the following structure was the main component. The phosphorus content was 5.6%.

[0127] [ka]

[0128] [Example 1] A 1000 ml separable flask was charged with 58.71 g of BTDA (0.1819 mol), 87.01 g of DDA (0.1629 mol), 4.28 g of VAB (0.0181 mol), 210 g of NMP and 140 g of xylene, and mixed thoroughly for 1 hour at 40° C. to prepare a polyamic acid solution. The polyamic acid solution was heated to 190° C., heated and stirred for 10 hours, and 125 g of xylene was added to prepare polyimide solution 1 (solid content: 32.7 wt %, weight average molecular weight: 56,611, thermoplastic polyimide) in which imidization was completed, and this was named polyimide varnish 1a.

[0129] [Example 2] 5.6 g of phosphorus-containing vinylbenzyl ether compound B, 6.5 g of elastomer resin 1, and 0.3 g of Perbutyl P (trade name, manufactured by NOF Corporation) were mixed with 100 g of polyimide solution 1 prepared in Example 1, and the mixture was diluted with xylene and NMP to a solid content of 30% by weight, and stirred to prepare polyimide varnish 2a.

[0130] [Example 3] A polyamic acid solution was prepared by charging 59.97g of BTDA (0.1857 mol), 83.51g of DDA (0.1563 mol), 6.52g of VAB (0.0276 mol), 210g of NMP and 140g of xylene into a 1000ml separable flask and mixing thoroughly at 40°C for 1 hour. The polyamic acid solution was heated to 190°C, heated and stirred for 10 hours, and 125g of xylene was added to prepare polyimide solution 2 (solid content: 31% by weight, weight average molecular weight: 52,515, thermoplastic polyimide) in which imidization was completed, and this was named polyimide varnish 3a.

[0131] [Example 4] 5.6 g of phosphorus compound B, 6.5 g of elastomer resin 1, and 0.3 g of perbutyl P were mixed with 100 g of polyimide solution 2 prepared in Example 3, and the mixture was diluted with xylene and NMP to a solid content of 30% by weight, and stirred to prepare polyimide varnish 4a.

[0132] [Example 5] A polyimide varnish 5a was prepared in the same manner as in Example 4, except that the amount of phosphorus compound B was 7.5 g.

[0133] [Example 6] A polyimide varnish 6a was prepared in the same manner as in Example 4, except that 7.5 g of phosphorus compound C was used instead of 5.6 g of phosphorus compound B.

[0134] [Example 7] A 1000 ml separable flask was charged with 71.81 g of 6FDA (0.1613 mol), 72.53 g of DDA (0.1358 mol), 5.66 g of VAB (0.0240 mol), 210 g of NMP and 140 g of xylene, and mixed thoroughly for 1 hour at 40 ° C. to prepare a polyamic acid solution. The polyamic acid solution was heated to 190 ° C., heated and stirred for 10 hours, and 125 g of xylene was added to prepare polyimide solution 3 (solid content: 32.6 wt%, weight average molecular weight: 54,197, thermoplastic polyimide) in which imidization was completed, and this was named polyimide varnish 7a.

[0135] [Example 8] A 1000 ml separable flask was charged with 56.73 g of BPDA (0.1924 mol), 86.52 g of DDA (0.1619 mol), 6.75 g of VAB (0.0286 mol), 210 g of NMP and 140 g of xylene, and mixed thoroughly for 1 hour at 40 ° C. to prepare a polyamic acid solution. The polyamic acid solution was heated to 190 ° C., heated and stirred for 10 hours, and 125 g of xylene was added to prepare polyimide solution 4 (solid content: 32.5 wt%, weight average molecular weight: 55,345, thermoplastic polyimide) in which imidization was completed, and this was named polyimide varnish 8a.

[0136] [Example 9] Polyimide varnish 9a was prepared in the same manner as in Example 4, except that elastomer resin 1 was not blended.

[0137] Comparative Example 1 A polyamic acid solution was prepared by charging 55.51 g of BTDA (0.1721 mol), 94.49 g of DDA (0.1735 mol), 210 g of NMP, and 140 g of xylene into a 1000 ml separable flask and thoroughly mixing at 40° C. for 1 hour. The polyamic acid solution was heated to 190° C., heated and stirred for 10 hours, and 125 g of xylene was added to complete the imidization to prepare polyimide solution 5 (solid content: 31% by weight, weight average molecular weight: 80,900, thermoplastic polyimide), which was named polyimide varnish 10a.

[0138] Comparative Example 2 1.12 g of N-12 was mixed with 100 g of the polyimide solution 5 prepared in Comparative Example 1, and the mixture was diluted with xylene and NMP to a solid content of 31% by weight, and stirred to prepare a polyimide varnish 11a.

[0139] Table 1 shows the formulations of Examples 1 to 9 and Comparative Examples 1 and 2.

[0140] [Table 1]

[0141] [Example 10] The polyimide varnish 1a prepared in Example 1 was applied to one side of a release-treated PET film, dried at 100°C for 5 minutes, then dried at 120°C for 10 minutes, and peeled off to prepare a resin sheet 1b (thickness: 25 μm). The various evaluation results for the adhesive sheet 1b are as follows. Dielectric constant: 2.7, dielectric tangent: 0.0017, flame retardant: Yes

[0142] [Example 11] A resin sheet 2b was prepared in the same manner as in Example 10 using the polyimide varnish 2a. The various evaluation results for the adhesive sheet 2b are as follows. Dielectric constant: 2.6, dielectric dissipation factor: 0.0015, tensile modulus: 0.5GPa, maximum elongation: 171%, Tg: 44℃, film retention: good, solder heat resistance test (dry): good, solder heat resistance test (moisture absorption): good, peel strength: 1.2kN / m, flame retardancy: good

[0143] [Example 12] A resin sheet 3b was prepared in the same manner as in Example 10 using the polyimide varnish 3a. The various evaluation results of the adhesive sheet 3b are as follows. Dielectric constant: 2.6, dielectric tangent: 0.0016, flame retardant: Yes

[0144] [Example 13] A resin sheet 4b was prepared in the same manner as in Example 10 using the polyimide varnish 4a. The various evaluation results of the adhesive sheet 4b are as follows. Dielectric constant: 2.6, dielectric dissipation factor: 0.0014, tensile modulus: 0.7GPa, maximum elongation: 199%, Tg: 49℃, film retention: good, solder heat resistance test (dry): good, solder heat resistance test (moisture absorption): good, peel strength: 1.2kN / m, flame retardancy: good

[0145] [Example 14] A resin sheet 5b was prepared in the same manner as in Example 10 using the polyimide varnish 5a. The various evaluation results of the adhesive sheet 5b are as follows. Dielectric constant: 2.6, dielectric dissipation factor: 0.0014, tensile modulus: 0.7GPa, maximum elongation: 162%, Tg: 46℃, film retention: good, solder heat resistance test (dry): good, solder heat resistance test (moisture absorption): good, peel strength: 1.1kN / m, flame retardancy: good

[0146] [Example 15] A resin sheet 6b was prepared in the same manner as in Example 10 using the polyimide varnish 6a. The various evaluation results of the adhesive sheet 6b are as follows. Dielectric constant: 2.7, Dielectric tangent: 0.0017, Tensile modulus: 0.8GPa, Maximum elongation: 183%, Tg: 49℃, Film retention: Good, Solder heat resistance test (dry): Good, Solder heat resistance test (moisture absorption): Good, Peel strength: 1.1kN / m, Flame retardancy: Good

[0147] [Example 16] A resin sheet 7b was prepared in the same manner as in Example 10 using the polyimide varnish 7a. The various evaluation results of the adhesive sheet 7b are as follows. Dielectric constant: 2.5, dielectric tangent: 0.0014, flame retardant: Yes

[0148] [Example 17] A resin sheet 8b was prepared in the same manner as in Example 10 using the polyimide varnish 8a. The various evaluation results of the adhesive sheet 8b are as follows. Dielectric constant: 2.7, dielectric tangent: 0.0015, flame retardant: Yes

[0149] [Example 18] A resin sheet 9b was prepared in the same manner as in Example 10 using the polyimide varnish 9a. The various evaluation results of the adhesive sheet 9b are as follows. Dielectric constant: 2.7, Dielectric tangent: 0.0016, Tensile modulus: 0.9GPa, Maximum elongation: 130%, Tg: 47℃, Film retention: Good, Solder heat resistance test (dry): Good, Solder heat resistance test (moisture absorption): Good, Peel strength: 0.5kN / m, Flame retardancy: Good

[0150] Comparative Example 4 A resin sheet 10b was prepared in the same manner as in Example 10 using the polyimide varnish 10a. The various evaluation results of the adhesive sheet 10b are as follows. Dielectric constant: 2.6, dielectric tangent: 0.0021, flame retardancy: ×

[0151] Comparative Example 5 A resin sheet 11b was prepared in the same manner as in Example 10 using the polyimide varnish 11a. The various evaluation results of the adhesive sheet 11b are as follows. Dielectric constant: 2.6, Dielectric loss tangent: 0.0021, Tensile modulus: 0.5GPa, Maximum elongation: 119%, Tg: 44℃, Film retention: Good, Solder heat resistance test (dry): ×, Solder heat resistance test (moisture absorption): ×, Peel strength: 1.0kN / m, Flame retardancy: ×

[0152] The above results are summarized in Table 2.

[0153] [Table 2]

[0154] From Table 2, it was confirmed that the resin sheets 1b to 9b of Examples 10 to 18, which had different resins, had a dielectric loss tangent of 0.0017 or less, high peel strength, and good solder heat resistance and flame retardancy, compared to the resin sheets 10b and 11b of Comparative Examples 4 and 5. From these results, it was confirmed that the adhesive sheet as a resin film according to the present embodiment can be expected to reduce transmission loss in a high frequency band of, for example, about 10 to 20 GHz, and has excellent peel strength, solder heat resistance, and flame retardancy while maintaining flexibility and film retention.

[0155] As shown in each of the above examples, polyimides made from aliphatic diamines and vinyl group-containing diamines showed clear improvements in dielectric properties, and furthermore, resin compositions using these polyimides showed improvements in peel strength, solder heat resistance, and flame retardancy.

[0156] From the above results, it was confirmed that the resin film according to the present embodiment can be suitably used as a material for circuit boards such as high-frequency compatible FPCs, for example, in various high-frequency signal transmission devices, such as for application to direct conversion type receivers.

[0157] Although the embodiment of the present invention has been described in detail above for the purpose of illustration, the present invention is not limited to the above embodiment, and various modifications are possible.

Claims

1. A polyimide containing a tetracarboxylic acid residue derived from a tetracarboxylic acid anhydride component and a diamine residue derived from a diamine component, the diamine residues derived from a dimer diamine composition mainly composed of a dimer diamine in which two terminal carboxylic acid groups of a dimer acid are substituted with primary aminomethyl groups or amino groups are contained in an amount in the range of 40 mol % or more and 95 mol % or less relative to the total diamine residues, 1. A polyimide comprising a diamine compound having a biphenyl skeleton or a naphthalene skeleton, the biphenyl skeleton or the naphthalene skeleton having at least one substituent having a carbon-carbon double bond selected from the group consisting of a vinyl group, an acrylic group, a methacrylic group, and an allyl group, in an amount of 5 mol % or more and 25 mol % or less relative to all diamine residues, the diamine compound having such a diamine residue.

2. A polyimide comprising a diamine compound having a biphenyl skeleton or a naphthalene skeleton, the biphenyl skeleton or the naphthalene skeleton having at least one substituent having a carbon-carbon double bond selected from the group consisting of a vinyl group, an acrylic group, a methacrylic group, and an allyl group, the amount of the diamine residue being in the range of 5 mol % or more and 25 mol % or less relative to all diamine residues, the polyimide being characterized in that, when formed into a film, the polyimide has a dielectric loss tangent (Tan δ) at 10 GHz of less than 0.002 after being conditioned for 24 hours under constant temperature and humidity conditions of 23° C. and 50% RH (normal state)

2. The following components (A) and (B): (A) the polyimide according to claim 1, and (B) a crosslinking agent, and the content of the (B) component relative to 100 parts by weight of the (A) component is within the range of 5 parts by weight or more and 30 parts by weight or less.

3. Furthermore, the following component (C): (C) an elastomer resin, and the content of the (C) component per 100 parts by weight of the (A) component is within the range of 5 parts by weight or more and 100 parts by weight or less.

4. Further, the component (D) is described below: (D) a polymerization initiator, and the content of the (D) component is within the range of 0.5 parts by weight or more and 2.0 parts by weight or less per 100 parts by weight of the (A) component.

5. A resin film comprising the polyimide according to claim 1.

6. The resin film according to claim 5, characterized in that after being conditioned for 24 hours under constant temperature and humidity conditions (normal state) of 23°C and 50% RH, the resin film has a dielectric loss tangent (Tan δ) at 10 GHz measured by a split post dielectric resonator (SPDR) of less than 0.

002.

7. A laminate having a substrate and an adhesive layer laminated on at least one surface of the substrate, A laminate, wherein the adhesive layer is made of the resin film according to claim 5 or 6.

8. A coverlay film having a coverlay film material layer and an adhesive layer laminated on the coverlay film material layer, A coverlay film, wherein the adhesive layer is made of the resin film according to claim 5 or 6.

9. A resin-coated copper foil in which an adhesive layer and a copper foil are laminated, 7. A resin-coated copper foil, wherein the adhesive layer is made of the resin film according to claim 5 or 6.

10. A metal-clad laminate having an insulating resin layer and a metal layer laminated on at least one surface of the insulating resin layer, 7. A metal-clad laminate, wherein at least one of the insulating resin layers is made of the resin film according to claim 5.

11. A circuit board obtained by wiring the metal layer of the metal-clad laminate according to claim 10.

Citation Information

Patent Citations

  • Lighting device for high frequency lamp

    JP1982077944A

  • Copper-clad laminate and circuit board

    JP2014069509A

  • Solvent-soluble polyimide resin

    JP2015180750A

  • Low-dielectric resin composition, cured product, dry film, film, prepreg, metal-clad laminate, printed wiring board and electronic apparatus

    JP2017125176A

  • Binding agent and article bound by binding agent

    JP2017137375A